SOCIAL ASPECTS OF THE OVERTOURISM PHENOMENON (PANGEEA, 2025)
The overtourism is a relatively little-known concept in Romania, despite being related to one of the most dynamic industries in the world, the tourism industry. Overtourism has been increasingly highlighted in recent years, in the context of changes in the hospitality industry and in connection with fluctuations in tourists' interest in certain destinations. The article outlines some key aspects of this phenomenon, strongly influenced by economic and cultural developments worldwide. Our focus is to provide a conceptual framework for a social analysis of overtourism.
Keywords: overtourism; tourists; locals; values; conflict